2011
DOI: 10.1002/jmv.22264
|View full text |Cite
|
Sign up to set email alerts
|

Antibody persistence and immune memory in adults, 15 years after a three‐dose schedule of a combined hepatitis A and B vaccine

Abstract: A combined hepatitis A and B vaccine is available since 1996. Two separate open-label primary studies evaluated the immunogenicity and safety of this hepatitis A and B vaccine (720 EI.U of HAV and 20 µg of HBsAg) in 306 healthy subjects aged 17-43 years who received three doses of the vaccine following a 0, 1, and 6 months schedule. These subjects were followed up annually for the next 15 years to evaluate long-term persistence of anti-HAV and anti-HBs antibodies. The subjects whose antibody concentrations fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…[15][16][17][18][19][20][22][23][24][25][26] The post-challenge SPRs and GMTs observed in this extension study were also comparable to or higher than those reported at the end of the primary vaccination series (Dose 3) for both groups (HBvaxPRO Ò group: 79.5% and 152.9 mIU/mL, respectively, at the end of the primary study, and 85.2% and 957.4 mIU/mL, respectively, post-challenge; Engerix B TM group : 88.3% and 437.2 mIU/mL, respectively, at the end of the primary series, and 88.3% and 1,497.6 mIU/mL, respectively, postchallenge).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][22][23][24][25][26] The post-challenge SPRs and GMTs observed in this extension study were also comparable to or higher than those reported at the end of the primary vaccination series (Dose 3) for both groups (HBvaxPRO Ò group: 79.5% and 152.9 mIU/mL, respectively, at the end of the primary study, and 85.2% and 957.4 mIU/mL, respectively, post-challenge; Engerix B TM group : 88.3% and 437.2 mIU/mL, respectively, at the end of the primary series, and 88.3% and 1,497.6 mIU/mL, respectively, postchallenge).…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Booster vaccinations are reported to be very effective in older individuals in case of inadequate response to primary vaccination. 12 Routine booster vaccination is not usually recommended for children or adults 3,19,20,[24][25][26] as it is difficult to identify individuals who would benefit from the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After full vaccination, the rate of seropositivity for anti-HAV ranged from 96.2% to 100%, regardless of the schedule used or whether the study was done in adults or children (Tables 2-4) [11,12,14,[18][19][20][22][23][24][25][27][28][29][30]32,[34][35][36][37]. Two articles reported lower seropositivity rates at month 7.…”
Section: Twinrix Tmmentioning
confidence: 99%
“…After the third dose, the GMC ranged from 2747 to 8895 mIU/ml [11,12,14,19,20,[22][23][24][25][27][28][29][30]34,35], which is well above the seropositivity cut-off levels, inferring seroprotection. However, GMC decreased with increasing age and body mass index (BMI) [23,27,33] was lower in HCV-positive adults [12], and it was lower in smokers compared to nonsmokers [24,27].…”
Section: Twinrix Tmmentioning
confidence: 99%
See 1 more Smart Citation